Epstein-Barr virus-positive diffuse large B-cell lymphoma, not otherwise specified: A diagnostic challenge (Indian Journal of Case Reports, 2020)
Epstein-Barr virus-positive (EBV+) diffuse large B-cell lymphoma (DLBCL), not otherwise specified (NOS) is an entity included in the 2016 World Health Organization classification of lymphoid neoplasms. EBV+DLBCL, NOS, is an aggressive B-cell lymphoma associated with chronic EBV infection and poor prognosis with standard chemotherapeutic approaches. We present the case of a 71-year-old male hospitalized for generalized lymphadenopathy, unexplained weight loss, and intermittent fever with pancytopenia and a very high EBV viral load. An inguinal lymph node was biopsied and reported at two different centers as Classic Hodgkin lymphoma and EBV associated lymphoproliferative, respectively. The patient was subsequently rebiopsied and a cervical lymph node was subjected to detail histopathologic and immunohistochemical evaluation by clonality studies resulting in a final diagnosis of EBV positive DLBCL, NOS. This case highlights the potential diagnostic pitfalls due to the morphologic heterogeneity of this entity and immunohistochemical overlap with Hodgkin lymphoma, T-cell rich large B-cell Lymphoma, and diffuse large B-cell lymphoma (DLBCL, NOS).